The Influence of Brand Image and Electronic Word of Mouth on the Purchase Intention by Data Packages IM3 Prepaid Card for Generation Z in Surabaya - Shafa, Alfi Syakilah Mayah; Soebiantoro, Ugy (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine the influence of brand image and electronic word of mouth on purchasing interest in prepaid IM3 card data packages. Brand image and electronic word of mouth are considered as factors that can influence a person's interest in purchasing a product. This research targets Generation Z who live in the Surabaya area, with a total of 99 respondents. The sampling technique used purposive sampling with the following respondent criteria: 1) have a smartphone, 2) have a social media account, 3) have a IM3 Simcard. Data analysis in this study using Partial Least Square. The results of this research show that: 1) Brand Image has no effect on purchasing interest in prepaid IM3 card data packages. 2) Electronic Word of Mouth has a positive and significant effect on purchasing interest in prepaid IM3 card data packages.